Reflexiones sobre las órdenes de no revivir (reanimar, resucitar) y suspender todo tratamiento. (Colombia Medica, 1996)
Reflexiones sobre las órdenes de no revivir  (reanimar, resucitar) y suspender todo tratamiento.